Eckweek, Peasedown-St-John, Somerset : survey and excavations at a shrunken medieval hamlet 1988-1990 - Young, Andrew, 1960-; Kidd, Alexander (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"This volume presents the results of archaeological survey and excavation at Eckweek, Somerset, which yielded one of the most important medieval rural settlement sequences yet excavated from south-west England. At the centre of the narrative is a succession of well-preserved buildings spanning the late 10th to the 14th centuries A.D. forming the nucleus of a Domesday manor and its Late Saxon precursor. Detailed analysis of the structural sequence offers a new regional perspective on pre-Conquest earthfast timber architecture and its subsequent (12th-century) replacement by masonry traditions. Culminating in a richly preserved 14th-century farmhouse, including a very complete assemblage of structural and domestic objects, the structural archaeology provides an unusually refined picture of the internal organisation of later medieval domestic space within a rural farming setting. Detailed analytical attention is given to the abundant artefactual and environmental datasets recovered from the excavations (including prolific assemblages of medieval pottery and palaeonvironmental data) with a nuanced appraisal of their interpretative implications. Anyone with an interest in the dynamics and regional complexity of medieval rural communities will find this a stimulating and enlightening read."--
OCLC-licensed vendor bibliographic record.
Keywords: Excavations (Archaeology) -- England -- Somerset; Saxons -- England -- Peasedown Saint John; Eckweek Site (Peasedown Saint John, England); Peasedown Saint John (England) -- Antiquities; SOCIAL SCIENCE / Archaeology